Talent development in football: are young talents given time to blossom? - Sæther, S. A.; Solberg, H. A. (Sport, Business and Management, 2015)
Purpose - The purpose of this paper is to investigate to what degree football clubs recruit talents and give them playing time in matches. It also investigates if foreign players displace younger talents. Furthermore, it analyses to what degree the use of younger talents and foreign players influence the performances of clubs. Design/methodology/approach - The empirical data are from Norwegian elite clubs, and come from two web sites: www.altomfotball and www.nettavisen.no. The analyses were done by means of OLS-regressions. Findings - OLS-regressions showed that clubs that had many foreign players gave less playing time to U20 players than other clubs did. However, these clubs did not have fewer younger talents in the squad than other clubs did. This indicates that foreign players reduce the playing time being given to younger players, but not their ability to train with other teammates. The clubs that won the most points gave less playing time to U20 players (in terms of minutes). Surprisingly, the regression showed that the clubs that had most foreign players did not win more points than others. Research limitations/implications - Norwegian football clubs have significantly less financial resources than, for example, clubs in the big European football nations. Therefore, more research is necessary to find out whether the findings in this research corresponds with the pattern in other nations. Originality/value - So far, the discussions about these issues have mainly been based on anecdotal evidence and very little on the findings in academic research. Therefore, this research give new insight to a field that needs more empirical-based analyses